Quando o Santo é Forte: uma discussão sobre a insuficiência humana no documentário de Eduardo Coutinho - Hornhardt, Nathalie de Almeida (2014)
This study aims to investigate, based on characters testimony s from the documentary Santo Forte, directed by Eduardo Coutinho, the pursuit of individual happiness and the fulfillment of human insufficiency by their religious beliefs and experiences. Taking into account this purpose, the idea is to highlight, considering the term devised by Blaise Pascal and conceptualized by Luiz Felipe Pondé - human insufficiency - that men/people need and are dependent on the supernatural world, precisely to fill the void which is inherent and that haunts them. In view of their mystical experiences and religious trajectory, the film's characters show a greater acceptance to their lives, due to the communication that they have with the sacred. In other words, it is clear that the relationship which men have with gods and entities gives them hope in the face of their endless reserve/tendency to suffering. This research also focuses to make considerations about the men s dependence towards the supernatural, which is necessary to ensure perpetual and rational pursuit of individuals with regard to happiness and well-being. This is noticeable from the emphasis on utilitarianism - principle developed by Jeremy Bentham and John Stuart Mill that indicates a natural man s search towards happiness and for annulment of misery and pain